Correlation between Migraine Severity and Cholesterol Levels. Issue 7 (10th July 2014) - Tana, Claudio; Santilli, Francesca; Martelletti, Paolo; di Vincenzo, Angelo; Cipollone, Francesco; Davì, Giovanni; Giamberardino, Maria Adele
Abstract Introduction Several studies have documented increased cardiovascular risk factors, particularly hypercholesterolemia, in the migraine population with respect to controls. However, no studies have investigated the possible relationship between headache severity parameters and lipid serum levels. Methods This study evaluated the lipid asset in 52 migraine patients (17 with and 36 without aura) before and after treatment with drugs for migraine prophylaxis for 3 months. Results High frequency (HF, ≥ 8/month) and intensity (HI, ≥ 5 Numeric Rating Score) vs. low frequency (LF, < 8/month) and intensity (LI, < 5) of crises were associated with significantly higher cholesterol levels, both total (TC, HF vs. LF, P < 0.0001; HI vs. LI, P < 0.0001) and LDL (LDL‐c, HF vs. LF, P < 0.0001, and HI vs. LI, P < 0.0001). In treated patients, a significant decrease in number and intensity of crises was associated with a significant reduction of TC and LDL‐c (P < 0.001). A direct linear correlation was also found between frequency and intensity of crises and lipid levels (TC/frequency, P < 0.0001; TC/intensity, P < 0.0001; LDL‐c/frequency, P < 0.0001; LDL‐c/intensity, P < 0.0001). No significant difference was found in the evaluated parameters for the subgroups of patients with and without aura. Discussion This study shows a significant positive association between migraine frequency and intensity with total and LDL cholesterol, demonstrating for the first time a significant reduction of these lipid parameters after migraine prophylaxis. However, in view of the retrospective design of the study and the small population size, these results should be considered as preliminary, to be confirmed by future prospective controlled trials.